User-Centered Redesign of Dental Cheek Retractor Using Quality Function Deployment - Owen Sebastian; Rosnani Ginting; Aulia Ishak (TALENTA Publisher, 2026)
This study aims to redesign the cheek retractor to enhance patient comfort and clinical efficiency, reducing soft-tissue trauma caused by poor fitting and material rigidity in conventional devices. A two-phase Quality Function Deployment (QFD) approach was applied involving ten dentists to identify user needs. Phase I (House of Quality) translated these needs into technical characteristics, while Phase II mapped the prioritized characteristics to critical components for design improvement. The results showed that QFD Phase I prioritized technical specifications such as product weight and mechanical strength, whereas Phase II prioritized the structural material and the width adjustment mechanism. The improved design utilizes durable PC/ABS material capable of repeated sterilization, effectively reducing tissue trauma, increasing comfort, and providing adjustable fitting for various oral anatomies. Overall, this study offers an innovative, QFD-based framework that directly links the voice of the dentist to engineering specifications to develop ergonomic and user-centered medical instruments.